-6x+6=4x+6

Simple and best practice solution for -6x+6=4x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x+6=4x+6 equation:


Simplifying
-6x + 6 = 4x + 6

Reorder the terms:
6 + -6x = 4x + 6

Reorder the terms:
6 + -6x = 6 + 4x

Add '-6' to each side of the equation.
6 + -6 + -6x = 6 + -6 + 4x

Combine like terms: 6 + -6 = 0
0 + -6x = 6 + -6 + 4x
-6x = 6 + -6 + 4x

Combine like terms: 6 + -6 = 0
-6x = 0 + 4x
-6x = 4x

Solving
-6x = 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-6x + -4x = 4x + -4x

Combine like terms: -6x + -4x = -10x
-10x = 4x + -4x

Combine like terms: 4x + -4x = 0
-10x = 0

Divide each side by '-10'.
x = 0.0

Simplifying
x = 0.0

See similar equations:

| -6m=-2n-4n | | 4n-10-3+n= | | 3.5x=161 | | x^2+y^2-6x+18y+74=0 | | 7x+1=22+4x | | 3=1.5n | | 4x+7-8x+10= | | 7x-10=3x+30 | | 550=45+315 | | 7x-2=4x+13 | | 49=k^2 | | 6-10x+8x=-34 | | 10-7x=-4x+7 | | -5x-6x=22 | | 18x+9=9x+47 | | 4-3x=4x-45 | | (4-8)= | | -7(9-6x)=287 | | 4+2x=-2x-8(5x+5) | | -3(8)+4=y | | 2x-3+103=180 | | .25(12x-8)=7 | | -24=7+4(f-8) | | 2+7x=x+38 | | 4(1+6x)=4-x | | (7x+6)+(5x+3)=(3x-9) | | 3(8)+4=y | | 7x+9=x-21 | | 3x^2-195x-46590=0 | | 5x-4=4+10x | | -24=7+4 | | b-4/9=12/5 |

Equations solver categories